2016
DOI: 10.1534/genetics.116.193896
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Checkpoint Kinase Chk1 by Reactive Oxygen Species Resulting from Disruption of wat1/pop3 in Schizosaccharomyces pombe

Abstract: DNA double-strand breaks are critical lesions that can lead to chromosomal aberrations and genomic instability. In response to DNA damage, Chk1, a serine/threonine kinase, is responsible for cell cycle arrest to prevent damaged cells from progressing through the cell cycle. Here, we report that the disruption of wat1, a WD repeat-containing protein, leads to the phosphorylation of Chk1. The double-deletion of chk1 and wat1 had a grave effect on the survival of fission yeast cells, and the spontaneous recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Abrogation of Wat1 in tor2-287 mutant background leads to synthetic lethality Tor2, a component of TOR complex 1 (TORC1) is responsible for promoting vegetative growth and suppresses sexual development [4]. Earlier, we have shown the role of Wat1, an important component of TORC1 and TORC2 in oxidative stress response and sexual differentiation [20]. Further to analyse the genetic interaction between tor2 and wat1, we tried to construct a double mutant of wat1Δ with a tor2-287 mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abrogation of Wat1 in tor2-287 mutant background leads to synthetic lethality Tor2, a component of TOR complex 1 (TORC1) is responsible for promoting vegetative growth and suppresses sexual development [4]. Earlier, we have shown the role of Wat1, an important component of TORC1 and TORC2 in oxidative stress response and sexual differentiation [20]. Further to analyse the genetic interaction between tor2 and wat1, we tried to construct a double mutant of wat1Δ with a tor2-287 mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Fission yeast Wat1/Pop3, a WD repeats containing protein is an important component of both TORC1 and TORC2 and exhibits conditional synthetic lethality with chk1 knockout [19,20]. The mammalian LST8, also known as GβL (an ortholog of S. pombe Wat1), is also involved in nutrient and growth factormediated signalling to S6K1 [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Whitby lab has subsequently been influential in designing several variations of the tandem repeat assay and have been able to explain some of the more complex outcomes. These assays have been used to identify and characterize genes involved in DNA damage repair [67][68][69][70][71][72][73][74][75][76][77][78]. The investigators initially designed a system similar to the Schuchert and Kholi assay except that instead of ura4 + they placed a his3 + marker between the ade6 alleles ( Figure 3C) [79].…”
Section: Recombination At Repetitive Elementsmentioning
confidence: 99%
“…Its role in genomic stability and microtubule integrity has also been reported (Verma et al, 2014; Ochotorena et al, 2001). Previously, we have shown that the inactivation of Wat1 in fission yeast cells results in ROS accumulation that might affect the mitochondrial integrity (Ahamad et al, 2016). In this study, we investigated the role of Wat1 in the maintenance of mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 99%